Coaching by the internet: Intercontinental stroke analysis - Rushall, B. S.
This article is a demonstration of how modern technology supports an ever expanding universe of resources. It describes how Australian athletes are using resources in the United States virtually as if both were in the same city. It remains to be seen how many more applications using modern communications technology develop to enhance the coaching services of organizations in the quest for improved sporting performances. What is described is an Australian swimming organization taking underwater videos for stroke analysis at a morning training session, sending the videos to the USA for analysis, the analysis being performed, and the results being returned to Australia in time for delivery to the head coach and swimmer at the afternoon training session. Conclusions : It is not easy to prognosticate what will eventuate in a complex human movement such as a swimming stroke if a movement segment is altered. It is obvious that the slow head and shoulder actions have to be changed. The features of the "new" action that should be incorporated are as follows 1.Hold the face profile horizontal until the sweep-round after the outward pull is completed. 2.Lift the head and shoulders as quickly as possible attempting to avoid hyperextension of the thoracic spinal region. 3.The height of the head lift should be as low as possible. It is likely that the face profile will never exceed 60 degrees. 4.Have the head lead the speed of all these actions as well as using it to minimize the magnitude of movements. 5.The breathing, torso-lift movements have to be accomplished within the time of the inward scull and the initiation of the kick backward. This is a very short period and will require meticulous attention to adherence and execution.